IMPLEMENTASI KUOTA TENAGA KERJA PENYANDANG DISABILITAS GUNA MEWUJUDKAN PEMENUHAN HAK BEKERJA: (Study Perusahaan-Perusahaan di Kota Tangerang) - Riandi Pratama MZ; Susanto (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2023)
The number of persons with disabilities in Indonesia is increasing every year, therefore it is necessary to pay attention to the government and empower the ability of a person with disabilities so that they can work with competence according to company standards. This study aims to explore the quota of disabled workers in companies in Tangerang City. To obtain research data information, purposive sampling method is used to determine which companies can be the object of research. The selected company is a private company in Tangerang City. Interview method with the determination of informants through the snowball technique. The findings of this study are that the implementation of the quota for persons with disabilities in Tangerang City still does not fully meet the quota according to the mandate of Law Number 8 of 2016 concerning Persons with Disabilities, this can be seen from the monitoring results of the Tangerang City Manpower Office in 2022 that only 144 people with disabilities work and are spread across 7 companies in Tangerang City.